2013
DOI: 10.1517/14728222.2014.860447
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cox-2 in human breast cancer cells as a critical determinant of epithelial-to-mesenchymal transition and invasiveness

Abstract: These findings support the existence of a direct link between COX-2 overexpression, EMT and invasiveness in human breast cancer cells, emphasizing the role of hypoxic microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 47 publications
(23 reference statements)
3
73
0
1
Order By: Relevance
“…Their studies indicate that PGE-2-induced EGFR transactivation involves signal transduction via TGF-α and activated MMP. Other investigators have confirmed that co-expression of COX-2, PGE-2, and EGFR results in mitogenic activation in precancerous and cancerous tissues of multiple anatomic sites [135][136][137][138][139] . In a recent molecular study of COX-2 and EGFR in human breast cancer tissues from 55 patients, COX-2 expression was detected in cancer cells of more than 95% of specimens and EGFR expression was found to be dependent on COX-2 upregulation [140] .…”
Section: Mitogenesismentioning
confidence: 86%
See 1 more Smart Citation
“…Their studies indicate that PGE-2-induced EGFR transactivation involves signal transduction via TGF-α and activated MMP. Other investigators have confirmed that co-expression of COX-2, PGE-2, and EGFR results in mitogenic activation in precancerous and cancerous tissues of multiple anatomic sites [135][136][137][138][139] . In a recent molecular study of COX-2 and EGFR in human breast cancer tissues from 55 patients, COX-2 expression was detected in cancer cells of more than 95% of specimens and EGFR expression was found to be dependent on COX-2 upregulation [140] .…”
Section: Mitogenesismentioning
confidence: 86%
“…This chain of molecular events leads to dissociation of the adhesion complex, accumulation of unphosphorylated beta-catenin in the cell nucleus, activation of the nuclear receptor, PPARgamma, and stimulation of cell proliferation through transcription of cell cyclin genes. Recent molecular studies suggest that this mechanism is not limited to the colon; that is, induction of cyclooxygenase and increased PGE-2 can result in cellular beta-catenin accumulation, nuclear PPAR-gamma activation, and subsequent cell proliferation and carcinogenesis in a variety of tissues including the mammary epithelium [138,139] . …”
mentioning
confidence: 99%
“…Thus, Celecoxib was found to be effective in upregulating E-cadherin thus reversing the EMT in cell lines derived from head and neck squamous cancer, colon cancer, gastric cancer and breast cancer [101][102][103][104]. Another COX-2 inhibitor, Etodolac, had a similar effect in bladder cancer cell lines, where EMT reversal was also seen in vivo in xenografts of the human bladder cancer cell line T24 [105].…”
Section: Cox-2 Is Associated With Breast Cancer Invasion Via Emtmentioning
confidence: 93%
“…Activation of S1PR2-COX-2 is a key enzyme involved in production of prostaglandins and has been implicated in various cell transformations including cholangiocytes (21)(22)(23)(24)(25). Previous studies reported that CBAs induced COX-2 expression and promoted growth in human CCA cells in culture (15,16).…”
Section: Tca Induces Cox-2 Expression and Chronic Inflammation Viamentioning
confidence: 99%